2005
DOI: 10.1021/jp053547e
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into the Origin of Visible Light Photocatalytic Activity of Nitrogen-Doped and Oxygen-Deficient Anatase TiO2

Abstract: The spin-polarized plane-wave pseudopotential method, based on density-functional theory, has been used to calculate the electronic band structures and the optical absorption spectra of nitrogen-doped and oxygen-deficient anatase TiO2. The calculated results are in good agreement with our experimental measurements. These ab initio calculations reveal that the optical absorption of nitrogen-doped TiO2 in the visible light region is primarily located between 400 and 500 nm, while that of oxygen-deficient TiO2 is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

47
338
0
5

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 446 publications
(390 citation statements)
references
References 51 publications
47
338
0
5
Order By: Relevance
“…Electrons could be excited from the VB to the defects donor state (red dashed line) under visible light illumination. The lifetime of electrons in the defects donor state is much longer than that on the CB (Lin et al, 2005;Xing et al, 2013), which facilitates the formation of superoxide radicals by attachment of electrons to oxygen. Meantime, the holes left in the VB accelerate the generation of free OH radicals.…”
Section: Effect Of Defect Disordersmentioning
confidence: 99%
See 2 more Smart Citations
“…Electrons could be excited from the VB to the defects donor state (red dashed line) under visible light illumination. The lifetime of electrons in the defects donor state is much longer than that on the CB (Lin et al, 2005;Xing et al, 2013), which facilitates the formation of superoxide radicals by attachment of electrons to oxygen. Meantime, the holes left in the VB accelerate the generation of free OH radicals.…”
Section: Effect Of Defect Disordersmentioning
confidence: 99%
“…It was found that doping of TiO 2 with nonmetal elements improved the visible light activity, depending on the type and the concentration of nonmetal dopants. Among the various nonmetal dopants, N-doped TiO 2 is widely used in photooxidation of organics (Lin et al, 2005;Chen and Burda, 2008;Gai et al, 2012) and in CO 2 photoreduction as well (Varghese et al, 2009;Fan et al, 2011;Zhang et al, 2011;Li et al, 2012;Zhang et al, 2012). However, the origin of the visible light activity of N-doped TiO 2 has long been debated.…”
Section: Electron Transfer From the Impurity State To Tio 2 Cbmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, N-doped TiO 2 is considered to be a promising photocatalyst, and it has been investigated widely, both by experimental and theoretical methods [2]. However, due to strongly localized N 2p states at the top of valence band [3], the photocatalytic efficiency of N-doped TiO 2 decreases because isolated empty states trap an appreciable proportion of photo-excited electrons and reduce photo-generated current [4]. Besides N-doped TiO 2 , C-doped TiO 2 also shows photocatalytic activity under visible-light [5].…”
Section: Introductionmentioning
confidence: 99%
“…3 lead to TiON samples with a higher optical absorption (Subramanian et al, 2011) due to the introduction of Ninterstitial sites doping the TiO 2 with O-vacancies (Valentin et al, 2005). This in turn leads to a larger amount charge transfer sites in the visible region (Lin et al, 2005;Lee et al, 2009 …”
Section: Coating Thicknesses In Relation To Bacterial Inactivationmentioning
confidence: 99%